2004
DOI: 10.1292/jvms.66.1359
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Final Dilution Rate, Sperm Concentration and Times for Cooling and Glycerol Equilibration on Post-Thaw Characteristics of Canine Spermatozoa

Abstract: ABSTRACT. This study re-evaluated a protocol for cryopreservation of canine semen. Semen from 4 beagle dogs was pooled, concentrated by centrifugation and adjusted to increasing sperm concentrations by adding back seminal plasma. The prepared or original semen was diluted with an extender (Egg yolk-Tris-citrate-glucose) and cooled to 4°C (cooling), followed by a second dilution with the same extender including glycerol, equilibrated at 4°C (equilibration), then stored in liquid nitrogen. The semen was diluted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
21
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 24 publications
2
21
2
Order By: Relevance
“…It is known that there is a great variability among species regarding sensitivity to injury caused by centrifugation. Thus, spermatozoa from rat (Cardullo and Cone 1986), human (Ng et al 1992;Alvarez et al 1993;Aitken and Clarkson 1988) and mouse (Katkov and Mazur 1998) are sensitive to centrifugal forces, but spermatozoa from other species are not (dog, Okano et al 2004b;stallion, Cochran et al 1984;Sieme et al 2004;Brinsko et al 2000;Crockett et al 2001;Waite et al 2008;bull, Pickett et al 1975;and boar Carvajal et al 2004;Matas et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…It is known that there is a great variability among species regarding sensitivity to injury caused by centrifugation. Thus, spermatozoa from rat (Cardullo and Cone 1986), human (Ng et al 1992;Alvarez et al 1993;Aitken and Clarkson 1988) and mouse (Katkov and Mazur 1998) are sensitive to centrifugal forces, but spermatozoa from other species are not (dog, Okano et al 2004b;stallion, Cochran et al 1984;Sieme et al 2004;Brinsko et al 2000;Crockett et al 2001;Waite et al 2008;bull, Pickett et al 1975;and boar Carvajal et al 2004;Matas et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Previous study compared the effects of low (5 × 10 6 sperm/ml) and high sperm concentrations (5 × 10 7 and 5 × 10 8 sperm/ml) on the cryosurvival of sperm from rhesus macaques and revealed that post-thaw sperm motility was not affected when sperm were cryopreserved at high concentrations [26]. Another study showed that different sperm concentrations within a tested range (up to 10 times) did not affect the post-thaw characteristics of canine sperm [27]. In our study, all of the rhesus macaque sperm samples were frozen at high sperm concentrations (ranging from 1.9 × 10 7 to 2.0 × 10 8 sperm/ml, calculated from Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Many investigations into the cryobiology of spermatozoa in dogs have been reported (Bouchard et al, 1990;Farstad, 1996;Hay et al, 1997;Okano et al, 2004;Rota et al, 1995;Songsasen et al, 2002;Thirumala et al, 2003). In addition, reports on oocyte maturation, in vitro fertilization, and embryo culture have been published (Renton et al, 1991;Yamada et al, 1992;Yamada et al, 1993).…”
Section: Dogsmentioning
confidence: 99%